FarmBuddy: Connecting Farmers and Customers for Local, Quality Produce - Karande, Shital; Menkudale, Shruti; Chopade, Ashwini; Darane, Maya; Jadhav, Gayatri (International Journal of Computer Sciences and Engineering, 2025)
The FarmBuddy App helps people easily find and buy fresh fruits and vegetables. It helps to customer discover nearby farmers markets, see what suppliers have available, and learn about where the products come from and their prices. For farmers, the app acts as a marketplace to features their products, keep track of what they have for sale, and connect directly with customers. The Farmers Market App is a dynamic mobile platform designed to connect local farmers directly with consumers, fostering the farm-to-table experience while promoting sustainable agriculture. As demand for fresh, organic produce rises, this app addresses the growing consumer interest in supporting local economies and accessing quality food. By offering real- time inventory updates, location-based services, and online ordering capabilities, the app enhances convenience and efficiency for both farmers and consumers. Additionally, it cultivates community engagement through user reviews and educational resources, empowering users with knowledge about sustainable practices and seasonal eating. Ultimately, the Farmers Market App aims to revolutionize the local food system, creating a vibrant marketplace that supports farmers and nurtures healthier communities. The Farmers Market App is an innovative mobile platform designed to connect local farmers with consumers, enhancing the farm-to- table experience while promoting sustainable agriculture. This app addresses the increasing demand for fresh, organic produce and the desire for consumers to support local economies.